Translating Genre of News Stories and the Correlated Grammar in Analysing Student Translation Errors - Choi, Gyung (Meta, 2013)
In translation studies, genre and grammar have each flourished in their own right as a subject of study by a number of scholars. But research solely dedicated to the complementary relations between genre and grammar has been rare, particularly from the translation education perspective. Neither genre nor grammar can function properly without the other in a text because context (genre) and ‘wording’ (grammar) are inseparable. The aim of this paper is to examine the correlation between genre structure and grammar in the analysis of errors in student translations of news story texts. Drawing on Systemic Functional Linguistics (SFL), translations of two subtypes of news-reporting texts from English to Korean are analyzed. The main data include two source texts and their translations by nine Masters’students. The findings of this paper show that a large majority of translation mistakes arise from a lack of knowledge of genre structure and its interconnection with logical meaning (how clauses, sentences and paragraphs are combined). The research reported in this paper indicates that genre structure and grammar together constitute useful resources for teaching the translation of news-reporting texts, with more studies of genre structure in other subject fields desired.